Artificial Intelligence (AI) is being Swiftly Integrated into Various Application Domains - Ihor Hunko (Multidisciplinary Journal of Akseprin Indonesia, 2024)
Artificial intelligence (AI) is quickly being used in areas like self-driving cars, healthcare, and cybersecurity, so there is a growing need for dependable and strong AI systems in these changing environments where conditions can be unpredictable. Traditional software testing methods that depend on set test cases and fixed situations often fail Traditional software testing methods that use fixed test cases and scenarios often fail to effectively handle the complexities of modern AI systems, which can result in hidden problems and security risks. This study will evaluate adaptive testing methodologies employing reinforcement learning (RL), fuzz testing, and other hybrid techniques for their application in software reliability assurance across various environments, including stable, low-resource, high-load, and adversarial contexts. The study is based on a series of experiments involving conversational chatbots, fraud detection systems, and autonomous navigation modules, illustrating that RL-adaptive testing methods enhance defect detection by 35-47% in dynamic environments relative to static testing methods and attain 40-50% increased stability under stress (pertaining to the system itself). Reinforcement learning (RL)-based approaches reduced failure rates by 75% compared to traditional testing methods. Fuzz testing was useful for finding edge cases, but it was less stable in adversarial situations when the same edge cases were used again. Moreover, the article delineates significant issues in AI Software Testing, such as environmental drifts and non-deterministic outputs, which are perceived to be more effectively addressed by reinforcement learning-based methodologies. Even though there is a balance between how easy it is to understand and the complexity of computing, the evidence shows that adaptive testing can greatly improve safety-critical systems and highlights the benefits of combining reinforcement learning's ability to optimize dynamically with fuzz testing's ability to find unusual problems. This document delineates application areas, providing explicit advice for developers and engineers to enhance the safety and reliability of AI in practical systems.